Opposition to Israel's first Qadiya. Issue 2 (14th March 2020) - Jacobs, Sarah
ABSTRACT: In 2017, following a fraught 22-year struggle, Israel appointed the first female judge (sing. qadiya, pl. qadiyat ) to its Islamic ( shari'a ) courts. This contrasts with the earlier appointments of qadiyat around the world, most notably in the Palestinian Authority in 2009. The Israeli shari'a courts' jurisdiction over family law, a field of law which engages in women's issues, makes the introduction of qadiyat particularly salient. This article is among the first to focus academic research on the issue of qadiyat within Israel and is based on field interviews with practitioners and academic experts, as well as documentary primary and secondary sources. This article finds that the obstacles that delayed the appointment of Israel's first qadiya were a manifestation of the political impact Muslim minority status had on the country's Muslim and Jewish establishments.